Predictors of self-reported hypertension among women of reproductive age in North Dakota - Corey A. Day; Grace Njau; Matthew Schmidt; Agricola Odoi (BMC Public Health)
Abstract Background Understanding the risk factors of hypertension among women of reproductive age (18–44 years) is important for guiding health programs aimed at reducing the burden of hypertensive disorders in this population. Therefore, the objective of this study was to investigate predictors of self-reported hypertension among women of reproductive age in North Dakota. Methods Behavioral Risk Factor Surveillance System data for the years 2017, 2019, and 2021 were obtained from North Dakota Department of Health and Human Services. A conceptual model was used to identify potential predictors of hypertension including sociodemographic characteristics, behavioral factors, chronic health conditions, and healthcare access. A multivariable binary logistic regression model was then used to identify significant predictors of hypertension. The predictive ability of the final model was assessed using a Receiver Operating Characteristic (ROC) curve and area under the curve (AUC). Results The odds of hypertension were significantly higher among women of reproductive age who reported frequent mental distress (odds ratio [OR] = 2.0, 95% confidence interval [CI] = 1.3–3.3), resided in a primary care health professional shortage area (OR = 1.8, 95% CI = 1.2–2.6), were obese (OR = 2.6, 95% CI = 1.7–4.1) and were 35–44 years old (OR = 2.3, 95% CI = 1.6–3.4), relative to their counterparts who did not have frequent mental distress, did not reside in a health professional shortage area, had a normal body mass index, and were 18–34 years old, respectively. Additionally, the odds of hypertension were lower among women who did not have a checkup within the last year compared to those who did have a checkup within the last year (OR = 0.6, 95% CI = 0.4–0.9). The AUC of the final model was 0.68. Conclusions There is evidence that frequent mental distress and disparities in healthcare access or utilization are predictors of hypertension among women of reproductive age in North Dakota. Further research is warranted to determine whether improved mental health can reduce the risk of hypertension in this population. Public health officials may consider promoting hypertension awareness and control programs in areas with limited access to healthcare professionals.